Improvement and validation of the heat transfer model for the containment module in the RCS-containment integral system code. (1st September 2020) - Ge, Li; Yang, Zijiang; Li, Huaqi; Shan, Jianqiang
Highlights: Coupling of nuclear reactor system codes and safety codes is increasingly important. Constitutive models must model flow regimes and gas condensation effectively. New models provide simulation results showing good agreement with experimental data. Abstract: Owing to improvements in containment systems of nuclear power plants, the coupling analysis of reactor system codes and containment codes is increasingly important for the thermal–hydraulic analysis of existing and future reactors. Extending reactor system code capabilities to allow them to simulate containment phenomena is of considerable current interest. In this paper, constitutive models for the containment module will be introduced in detail, with special focus on the flow regime for large spaces and the wall condensation model in the presence of noncondensable gases. The improved constitutive models have been validated by comparing simulation results with available experimental data from wall and in-pipe steam-noncondensable gas experiments and the PUMA GDLB test. The calculation results showed that the improved constitutive models for the containment module better predict the experimental phenomena with higher accuracy.